GUARDIANS OR CARRIERS? : What Bats and Rodents Reveal About Emerging Diseases - Faisal Ali, Anwarali Khan (UNIMAS Publisher, 2025)
Small mammals are recognised as reservoirs for zoonotic diseases, many of which can be transmitted to humans. Factors such as urbanisation, deforestation and climate change further intensify the spread of these diseases by altering habitats, influencing animal behaviour and expanding the geographical range of certain pathogens. Even relatively undisturbed forests can harbour novel or previously uncharacterised bacteria within their small mammal populations. Among these, bats and rodents are of interest due to their frequent associations with zoonotic pathogens.